(untitled) (Bangladesh Journal of Public Administration, 2025)
Bangladesh has been addressing chronic poverty since 1971 through social security programs, primarily in rural areas. Urbanization has increased the number of urban poor, and the Open Market Sale program has not been significantly improved. This study aims to assess the Grievance Redress Mechanism of the OMS program in this country. This study employed a qualitative methodology and an exploratory research design. A total of 20 in-depth interviews (IDIs) were conducted with carefully selected beneficiaries, while 10 key informant interviews (KIIs) were carried out with program administrators, local vendors, and community leaders to gather primary data. Secondary data were gathered by analyzing government reports, research articles, and reports on the Grievance Redress Mechanism of the OMS program. The study found that the method is not being effectively implemented since the beneficiaries are unable to comprehend the instructions due to the lack of clarity in the online system. Moreover, the beneficiaries’ apprehension towards the corrupt officials and the merchants’ affiliations with political elites deter them from expressing their grievances against them. The authorities should prioritize the effective implementation of the grievance redress mechanism of the OMS program, as the input of multiple perspectives is crucial for the success of this program.